The concept of «Tree» in the culture of Central Asia (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the substantial components of the concept of«Tree». Universal, nationalcultural and individual layers are identified. Itholds indetail description of the «layer» of the concept of «Tree». As thematerial of description the works of the famous contemporary writer B.Kanapianov were considered. The researcher highlights language meansthat represent the concept of «Tree». The focusing on the context of language units representing the concept of «Tree» gives an opportunity toreveal the periphery of the concept, to describe the meaning shades thatare not fixed in any lexicographical sources, and finally to discover thepeculiarities of studied concept in linguocultural aspect. The technique ofthe conceptual analysis presented in the article can be used at research oflanguage of any work of art.
Keywords: concept; representation of the concept; picture of the